Sistem Monitoring Jaringan Sensor Node Berbasis Protokol MQTT - Muhammad Diono; Hamid Azwar; Wahyuni Khabzli (Politeknik Caltex Riau, 2021)
n this study, the implementation of a sensor node monitoring system based on the MQTT protocolis presented. The sensor node is made using the NodeMCU ESP8266 which is connected to thesensor to measure temperature, humidity, gas levels, and the presence of fire. Nodered is used tobuild a monitoring system. In this study, four connected sensor nodes were used. The MQTTprotocol is implemented on both sides of the sensor node and monitoring system. The sensor nodewill act as a publisher and the monitoring system will act as a subscriber. The sensor dataobtained will be sent to the monitoring system using the MQTT protocol. The test results showedthat the MQTT protocol was successfully implemented. Data from all sensor nodes can bedisplayed on the monitoring system